Serum Immunoglobulin Levels in Type 2 Diabetic Patients in Korle-Bu Teaching Hospital, Ghana - Botchey, C.P.K (University of Ghana, 2014)
The incidence of type 2 diabetes is on the increase and on-going research suggests that the increased concentrations of some circulating immunoglobulins among type 2 diabetic patients may be non-specific signs of the development of diabetic complications. Immunoglobulins, of which the most abundant are IgA, IgG and IgM, play an essential role in the body’s immune system by assisting in destroying foreign substances when they invade the body. Elevated immunoglobulin levels have however been strongly linked to the development and progression of diabetic complications. The aim of this study was to investigate serum levels of immunoglobulins (IgA, IgG and IgM) in Ghanaian type 2 diabetics, and to identify factors that may be associated with the variation in immunoglobulin levels that may lead to diabetic complications. One hundred and ninety two (96 type 2 diabetic and 96 non-diabetic) subjects were recruited for the study. Diabetic subjects were contacted during outpatient clinic appointments at the National Diabetes Research and Management Centre, Korle-Bu Teaching Hospital. Matched non-diabetic controls were recruited from the catchment area. The immunoglobulins (IgA, IgG and IgM) and interleukin 6 (IL-6) concentrations were measured in subjects sera using commercially available ELISA assays performed according to manufacturer’s instructions. Blood chemistry, blood pressure, body mass index and waist circumference of subjects were assessed. Serum IgA (g/L) was higher in the diabetic than in the non-diabetic subjects (0.89 vs 0.74, p=0.043). Serum IgG (g/L) was also significantly higher in the diabetic compared with the non-diabetic subjects (7.58 vs 7.29, p<0.001). The difference in serum IgM between diabetics and the non-diabetics was not significant. Serum IL-6 (pg/mL) was higher (1.70) in Type 2 diabetic subjects than in the non-diabetics (0.99) (p<0.001). The results showed that waist circumference (WC) and body mass index (BMI) were significantly higher in the diabetics than in the non-diabetic subjects (p<0.001 in both cases). However, there were no relationships between the WC and the immunoglobulin levels; and BMI and the immunoglobulin levels. There was no significant correlation between BMI and IL-6 (p=0.337). Albumin, Low Density Lipoprotein (LDL), Very Low Density Lipoprotein, and cardiovascular risk (Total Cholesterol / HDL) did not show any significant association with the immunoglobulin levels. There was association between fasting blood glucose (FBG) and IgA (p=0.001). FBG was also associated with IL-6 (p=0.025). Serum IgG levels inversely correlated with glycated haemoglobin (HbA1c) (p=0.036). Serum IL-6 showed significant correlation with both IgA (p=0.001) and IgM (p=0.003). It can be concluded that the serum immunoglobulin levels were elevated in the Type 2 diabetic subjects.
Thesis (MPhil) -University of Ghana 2014